The cross-border journey: exploring the unheard trauma, identity crisis, and perpetual pursuit for “Home” in Crossing and Americanah - Nanjeeba, Labiba Rifah (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.